Cinnabar use in Anyang of bronze age China: Study with micro-raman spectroscopy and X-ray fluorescence. (June 2022) - Liu, Jhih-Huei; He, Yuling; Ke, Weiying; Hwang, Ming-chorng; Chen, Kuang Yu
Graphical abstract: Highlights: For the first time cinnabar was shown on artefacts unearthed from Shang Ruins by Micro-Raman spectroscopy. For the first time cinnabar was confirmed in Shang coffin by micro-Raman and X-ray Resonance Fluorescence. The wide use of cinnabar, from decorative to mortuary use, would make cinnabar production a major Shang industry. Abstract: Anyang was the last capital of the Shang Dynasty ( ca . 1600–1050 BCE) of China. Archaeological excavations at Anyang since 1928 has yielded inscriptions and artifacts that authenticated the Shang history and enriched our understanding of their material culture and technical achievement. Here, we have performed micro-Raman spectral analysis of artifacts recovered from royal tombs unearthed last century at Yinxu, Anyang, including a block of colored clay impressed with motif from perished woodcrafts, a stone knife, a set of small bullet-shape bronze containers, and a pottery color-container. In addition, we used micro-Raman and X-ray fluorescence (XRF) to analyze the soil sample collected from the tomb M103 excavated at Wangyukou village, Anyang in 2009. The results showed that all red coloration on artifacts and coffin soils was due to cinnabar, suggesting a wide use of cinnabar in Shang society. We also showed that micro-Raman and XRF analysis can be carried out directly on soils adsorbed on Q-tip, providing a convenient means for future on-site soil sampling and spectral analysis of cinnabar in grave area. Based on literature information we estimated that the amount of cinnabar used in Shang society would make the scale of its production on par with other major industries, such as bones, jades, and bronzes.